Impact of Sample Aging on Freeze-Thaw Stability of Oil-in-Water Emulsions Prepared with Soy Protein Isolates - Palazolo, Gonzalo Gastón (2016)
The freeze-thaw stability of oil-in-water emulsions prepared with unheated and heated aqueous dispersions of fresh and stored soy protein isolates was evaluated in the absence and presence of glucose or sorbitol (0.75–15.0% w/w). Sample aging had a negative impact of freeze-thaw stability. The cryoprotectant addition enhanced the freeze-thaw stability, but at low concentrations emulsions prepared with unheated soy protein isolates showed better response to freeze-thawing. Nevertheless, at the highest cryoprotectant concentration, a total stabilization was evidenced for all emulsions. The results of this article indicated that the cryoprotectants act on proteins at interfacial level.